2019
DOI: 10.1016/j.cegh.2018.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Investigating prevalence of musculoskeletal disorders among Iranian nurses: A systematic review and meta-analysis

Abstract: Introduction: Musculoskeletal disorders are one of the most common and costly occupational injuries. Nursing profession, considering the nature of the work, is one of the occupations in hospital in which work-related musculoskeletal disorders are highly prevalent. This review study was conducted to determine the prevalence of musculoskeletal disorders among Iranian nurses. Materials and methods: The present study was conducted on the basis of the PRISMA checklist for systematic review and meta-analysis. To acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 29 publications
1
22
0
Order By: Relevance
“…The worldwide epidemiological studies have revealed a high incidence and prevalence of low back musculoskeletal complaints among nurses [4]. Furthermore, work-related musculoskeletal disorders (WMSDs) are among the leading causes of occupational diseases among healthcare professionals worldwide [5][6][7]. In a clinical setting, nursing personnel often must move, pull, or push patients to and from their beds or other locations, and such activities involve excessive bending or turning of the body [8,9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The worldwide epidemiological studies have revealed a high incidence and prevalence of low back musculoskeletal complaints among nurses [4]. Furthermore, work-related musculoskeletal disorders (WMSDs) are among the leading causes of occupational diseases among healthcare professionals worldwide [5][6][7]. In a clinical setting, nursing personnel often must move, pull, or push patients to and from their beds or other locations, and such activities involve excessive bending or turning of the body [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…A multicenter cross-sectional study by Clari et al [6] showed that 48.3% of operating room nurses reported one or more episodes of upper limb pain. Moreover, a systematic review and meta-analysis by Saberipour, Ghanbar, Zarea, Gheibizadeh, Zahedian [7] showed that the prevalence of MSD and lower back pain in nurses were 0.84 (95% CI: 0.83-0.95) and 0.60 (95% CI: 0.60-0.61) respectively. Kalkim, Midilli, and Dogru [16] conducted a survey on 498 nurses with MSDs.…”
Section: Introductionmentioning
confidence: 99%
“…They also exerted devastating effects on the personnel's health, quality of life, and job satisfaction and could lead to https://doi.org/10.1016/j.cegh.2020.03.019 Received 30 January 2020; Received in revised form 7 March 2020; Accepted 19 March 2020 loss of workdays. 12,13 Studies in the Europe demonstrated that almost 40 million workers (more than 30%) suffered from these disorders, accounting for 0.5-2% of the European Union's Gross Domestic Product (GDP). 2 Despite the high prevalence of MSDs in communities, healthcare personnel are faced more with these problems.…”
Section: Introductionmentioning
confidence: 99%
“…73 More evidence of lower back pain among nurses to convey the present study findings can also be found in the systematic review conducted by Pinar and Ali (2018). 74 The lower back was also the most affected body region in the systematic review and meta-analysis done by Saberipour et al (2019) among Iranian nurses. 77 D" Agostin and Negro (2017) crosssectional study also revealed that lower back pain was most prevalent among nurses.…”
Section: Years Of Employmentmentioning
confidence: 99%
“…74 The lower back was also the most affected body region in the systematic review and meta-analysis done by Saberipour et al (2019) among Iranian nurses. 77 D" Agostin and Negro (2017) crosssectional study also revealed that lower back pain was most prevalent among nurses. 78 More so, Tsekoura (2017) study showed that the lower back was mostly affected by MSD among nurses in Greece.…”
Section: Years Of Employmentmentioning
confidence: 99%